Child Maltreatment and Household Dysfunction in a British Birth Cohort. (27th February 2013) - Denholm, Rachel; Power, Chris; Li, Leah; Thomas, Claudia
<x xml:space="preserve">Abstract</x> Abstract In this article, we assess the prevalence of child maltreatments, their co‐occurrence and associations with household dysfunction in a large population cohort. Information from the 1958 British birth cohort on childhood abuse, neglect and household dysfunction recorded at 45 years and during childhood was used. Prevalence was calculated in three samples: individuals with each measure (n = 9310–15 583); 45‐year‐old participants (n = 9310); and all surviving to 45 years (n = 17 313) includes imputed data. A cumulative neglect score was derived. Latent Class Analysis (LCA) was applied to establish the co‐occurrence of maltreatments. In the three samples, 14.2 to 17.1 per cent of participants reported any form of abuse: psychological (10.0–12.5%), physical (6.1–9.0%), sexual (1.6–2.9%) and witnessing abuse (6.0–8.5%). A high neglect score (≥ 3; prevalence 25.9–32.1%) was positively associated with any form of abuse (30% increase/unit). LCA identified 8.2 per cent of participants at risk of both abuse and neglect, and 24.9 per cent at high risk of neglect 'only'. Measures of household dysfunction were associated with all types of child maltreatment, particularly with abuse and neglect. Approximately one‐third of this population sample showed a high risk of child maltreatment; over one in ten reported any form of abuse. Those from dysfunctional family backgrounds were particularly vulnerable to both child abuse and neglect. Copyright © 2013 John Wiley & Sons, Ltd. <boxed-text content-type="pullQuote" id="car2235-blk-0028" position="anchor" orientation="portrait"> 'Those from dysfunctional family backgrounds were particularly vulnerable to both child abuse and neglect' </boxed-text> Key Practitioner Messages What Is Known Child abuse and neglect are common and likely to co‐occur. Measures of household dysfunction are associated with child maltreatment. What This Study Adds Child maltreatments co‐occur in the 1958 cohort: one in three had an increased risk of neglect, and of these 25 per cent were at risk of abuse. Individuals from dysfunctional family backgrounds were at an increased risk of maltreatments in childhood. Dysfunctional family background was more strongly associated with abuse and neglect together than neglect alone.